The Inhibitory Potential of Botanical Fungicides Against Colletotrichum capsici the Causal Agent of Anthracnose on Chili in-Vitro - Sudania, Sudania; Ropalia, Ropalia; Kusmiadi, Riwan (CROPSAVER, 2023)
Colletotrichum capsici infection in chilies significantly affected the yields. The use of chemical fungicides to control this pathogen has negative effects on health and the environment. The use of botanical pesticides is one alternative to control C. capsici. This study aims to determine the effect of a type of plant extract with a certain concentration to effectively inhibit the growth of the C. capsici The study used a completely randomized design (CRD) with five levels of treatment and five times replication. The treatments were no treatment/negative control, chemical fungicide (contains 70% propineb)/positive control, papaya leaf extract (20%), betel leaf extract (25%), and galangal rhizome extract (30%). Each experimental unit was repeated three times, each repetition using duplo petridishes. The results showed that the treatment had a significant effect on the inhibition of C. capsici in the PDA medium. Botanical fungicide treatment with galangal rhizome extract (30%) was able to significantly inhibit the growth of C. capsici compared to betel and papaya leaf extracts, although it was not as effective as chemical fungicides (contains propinep 70%). The inhibitory abilities of galangal rhizome extract (30%) and chemical fungicide (70% propineb) were 8,34% and 19,91%, respectively.